Retail change in a context of an overtourism city. The case of Lisbon - Guimarães, Pedro (2021)
Abstract Purpose – The excess of tourism in some destinations has led to the discussion of overtourism. One of the sectors that most interacts with tourism is retail, a key element in the experience lived by tourists. The purpose of this paper is to analyse how retail evolves in a context of an overtourismcity, how it relates with touristification and what are the elements that best characterise such evolution and relation. Design/methodology/approach – This research is based on a case study, using the main historic city centre of Lisbon for that purpose. Fieldwork was developed by the author to collect information about the commercial fabric and itsmain characteristics. Findings – The findings show a clear adaptation of the commercial fabric of the analysed area to the tourism industry. Furthermore, the author unfolded that the change of retail is towards a consumption environment based on leisure, involving the adaptation of the public space into terraces, and on the thematisation of stores, using elements seen as ‘‘authentically’’ Portuguese, which bestows on theses spaces a sort of certification of quality and authenticity. Originality/value – The mere reference to the homogenisation of the retail fabric is too simple to explain the richness and variety of elements imbedded in the process of retail change in a context of excessive tourism and touristification. In this paper, the author produced novel knowledge by analysing the elements that embody the evolution of retail in such a context.